Teaching and learning developmental anatomy: exploring google classroom engagement through preferred usage, behavioural intentions, and actual practices - Ramakrishna, Roopashree (International Journal of Research in Medical Sciences, 2025)
Background: In the 21st century researchers, trainers and teachers have begun to design and implement variety of teaching methodologies using online technology to improve traditional face-to-face teaching. Blended learning improves student engagement. In education, blended learning environment offers the convenience of the online environment without losing face-to-face teaching, and interaction with the learners. Objectives of the study were: to compare/estimate the difference the effective learning between the traditional pedagogy blended learning activities through eLearning; and to know the perception of the blended learning experience through eLearning in using google classroom site. Methods: Regular classroom was used for traditional lecture and digital library for blended learning for the 1st MBBS students. Results: In our study we found digital learning did improve students test score significantly. Students found blended learning helpful for learning the topics chosen in embryology. About 95% of the students strongly agreed to the fact that blended learning in digital library is conducive for learning the developmental anatomy. Conclusions: During the study we found that blended learning environment is effective in teaching-learning embryology on students in terms of impact on learning and their perceived satisfaction. In the current study suggest that both preferred easy to use and preferred use positively affect the behavioral intention by undergraduates’ students who perceive the use of Google classrooms as easy and useful, and they are highly motivated toward the incorporation of such pedagogical tools in their learning process of developmental anatomy.